2022
DOI: 10.1038/s41598-021-04020-1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of animal model congruence to human depression based on large-scale gene expression patterns of the CNS

Abstract: Depression is a complex mental health disorder that is difficult to study. A wide range of animal models exist and for many of these data on large-scale gene expression patterns in the CNS are available. The goal of this study was to evaluate how well animal models match human depression by evaluating congruence and discordance of large-scale gene expression patterns in the CNS between almost 300 animal models and a portrait of human depression created from male and female datasets. Multiple approaches were us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 70 publications
1
8
0
Order By: Relevance
“…We recently used a depression portrait to identify animal models with congruence to depression 102 and ongoing useful steps could involve use of the AD portrait (or similar portraits) to evaluate and identify what animal model has the highest concordance with the AD brain signature. Advances in this area have already begun as a recent study identified mouse models that were congruent with coexpression modules found in AD 24 .…”
Section: Discussionmentioning
confidence: 99%
“…We recently used a depression portrait to identify animal models with congruence to depression 102 and ongoing useful steps could involve use of the AD portrait (or similar portraits) to evaluate and identify what animal model has the highest concordance with the AD brain signature. Advances in this area have already begun as a recent study identified mouse models that were congruent with coexpression modules found in AD 24 .…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the Ttr gene was found to be increased in both FSS and R-SDS mouse models, and Ttr overexpression induced depression-like behavior as measured by two different tests, the TST and PST. However, it is important to assess how well mouse models match human depression because some mouse models showed no relation to human depression in central nervous system gene expression changes [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to chronic stress, acute stress can induce protein phosphorylation and gene transcription in the hippocampus [ 17 ]. Several animal models for human depression have been used to identify gene expression patterns [ 18 ]. However, comparisons of gene expressions between different depression models or the identification of differentially expressed genes in multiple depression models have been scarcely explored, whereas previous studies have mainly focused on a single model in this context.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we contribute to on-going work by comparing and ranking expression patterns from 500 animal models with those from human AD. We include the new data from the GFAP mutation mice along with two independently curated model lists; one produced by us (over 300 models) in a study of human depression [ 25 ] and the other from Wan and colleagues (~ 200 models) [ 18 ] in a study of AD. This study focusses on congruence (similarity) of dysregulation in the model and AD (same direction of change) that uses a standardized cutoff and is independent of whether a gene is in a co-expression module or not.…”
Section: Introductionmentioning
confidence: 99%